Strategies for Teaching Geography Electives in English to Native Spanish Speakers at a Colombian University - Nohora Bryan; Ezana Habte-Gabr (Universidad de La Sabana, 2010)
Universidad de La Sabana in Colombia has been increasing course work in English, and the need for adequate learning and teaching strategies has become salient as both students and instructors expressed concern of a foreign language impeding content acquisition. Through a seminar on English Content-Based Instruction, the Foreign Languages Department identified underlying problems related to language, such as the need for language strategies in mainstream courses in areas such as academic writing and reading. The English Content-Based Instruction approach seeks to simultaneously teach content and language. The need for instruction to be focused on fostering autonomous learning became apparent given the heterogeneity of learning styles. Two geography courses taught in English are discussed here in light of an overall survey on learning strategies.